Depression in Diabetic Patients: What Is the Link With Eating Disorders? Results of a Study in a Representative Sample of Patients With Type 1 Diabetes - Pinna, Federica; Suprani, Federico; Deiana, Valeria; Lai, Lorena; Manchia, Mirko; Paribello, Pasquale; Somaini, Giulia; Diana, Enrica; Nicotra, Eraldo Francesco; Farci, Fernando; Ghiani, Mariangela; Cau, Rossella; et al. (Frontiers in Psychiatry, 2022)
Background and purpose: Comorbidity between diabetes and depression, and diabetes and eating disorders (ED) conveys significant diagnostic, clinical and therapeutic implications. The present study was conducted on a sample of adult outpatients affected by Type 1 Diabetes (T1DM) to assess lifetime prevalence of ED; current prevalence of depression and Disturbed Eating Behaviors (DEB) and their impact on glycemic control. We hypothesized that patients with depression would have higher rates of lifetime ED and current DEB. We hypothesized a significant and independent association between DEB and the prevalence of depression. Methods: The study was carried out using a cross-sectional design in a sample of 172 diabetic patients with T1DM aged from 17 to 55 years. Lifetime prevalence of ED according to DSM-5 criteria was assessed by means of the Module H modified of the Structured Clinical Interview for DSM-IV Axis I Disorder (SCID-I). The following questionnaires were used: Beck Depression Inventory - IA version (BDI-IA) and Diabetes Eating Problems Survey – Revised (DEPS-R), to assess respectively the current presence of depression and DEB. Socio-demographic, clinical and laboratory data were also collected. Results: High rates of depression (35.5%) and DEB (19.2%) were observed in our sample of 172 adult outpatients with T1DM. Lifetime history of ED was present in 20.9% of the sample and was more frequently diagnosed in patients with current depression (34.4% vs 13.9%, p=0.002). Higher levels of DEB at DEPS-R significantly increased the odds of depression (adjOR: 1.09; 95% C.I.: 1.03-1.15; p=0.003). The presence of DEB was associated with poor glycemic control. On the other hand, no association was found between depression and metabolic compensation. Conclusion: Adult patients with T1DM and depression should be screened for ED and DEB. Treating DEB could positively impact both mood and glycemic control in this population. Further studies should be carried out on a larger patient population using a longitudinal design and an accurate method of evaluation to explore the complex relationship between diabetes, depression, ED, and DEB. Future research should investigate treatment strategies for DEB in T1DM patients and their impact on both psychopathological and metabolic outcomes.